PENERAPAN STRATEGI PEMBELAJARAN BERORIENTASI AKTIVITAS SISWA DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH KELAS VII MTs.PP.DARUNNAJAH SUNGAI ALAH KECAMATAN HULU KUANTAN - Renawati Renawati; Sopiatun Nahwiyah; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2020)
This essay is entitle : Application of education strategg oriented to student activity in mereasing the student stady result in fiqih subject for VII grade MTs.PP. Darunnajah Sungai Alah Kecamatan Hulu Kuantan loth background the problem of student study result iq. The an that will be reach in this researd is to know how the application, of education strategi oriented to student activity in mereasing the student study result in fiqih subject for VII grade MTs.PP. Darunnajah Sungai Alah Kecamatan Hulu Kuantan Kabupaten Kuantan Singingi and factors influencing, thisresech do in 3 month. Thechnic for collecting the data is observation, interview and document. This research do in 3 cycle, this thing do to make the teacher can see the student study result from application of education strategg oriented to student activity. In the application of every cycle, the result of classical completnes increase 100 % is categorism as every high.